NILAI PASAR WAJAR SAHAM MILIK PT. BANK TABUNGAN NEGARA (Persero) TBK. PASCA HAK MEMESAN EFEK TERLEBIH DAHULU (HMETD), 2012 - , Zulkifli; , I Wayan Nuka Lantara, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to analyze the fair market value of shares of the PT Bank Tabungan Negara (Persero) Tbk. The analytical tool used in this study is Income Approach with Discounted Cash Flow method (DCF) and the Market Data Approach Relative Valuation method. The data used in this study are annual reports and the company's financial statements that have been audited by Public Accountant period from 2007 to 2011. Besides, it also used the regular presentation of data to the public and investors the company is available on the Company's website. Data were also obtained from customer service Central Agency on Statistics (BPS) and The Bank Indonesia website. By applying the DCF models in estimating the value of selected models-Free Cash Flow FCF yield the conclusion that the value of the fair market value for the 60 percent stake in PT. Bank Tabungan Negara (Persero) Tbk., owned by the Government (Majority) per December 31, 2012 amounted to Rp1.896,00 (one thousand eight hundred and ninety-six rupiah) per share and for a 40 percent stake in PT. Bank Tabungan Negara (Persero) Tbk., owned by Community (Minority) per December 31, 2012 amounted to Rp1.754,00 (one thousand seven hundred and fifty-four rupiah) per share. These results have been applied control premium of 30 percent and 20 percent market premium. At the end of the chapter the data analysis was also performed using a model calculation of Relative Valuation generating Indicative value of the Government (Majority) per December 31, 2012 amounted to Rp1.321,00 (one thousand three hundred and twenty-one rupiah) per share and to share Community owned (Minority) of Rp1.016,00 (one thousand and sixteen rupiah). These results have been applied control premium by 30 percent. A reconciliation of the two models above, with weights DCF models: Relative Valuation models by 60 percent: 40 percent of the value of the results obtained indications of the Government (Majority) for Rp1.666,00 (one thousand six hundred and sixty six rupiah) per share and for Community-owned shares (minority) for Rp1.459,00 (one thousand four hundred and fifty-nine rupiah), which belongs to the general public the price is not too different from the closing price of the Indonesia Stock Exchange (IDX) as at December 31, 2012 amounted to Rp1.470,00 (adj. closed) to PT Bank Tabungan Negara (Persero) Tbk. with the trading code BBTN.JK.